2012
DOI: 10.3945/jn.112.161372
|View full text |Cite
|
Sign up to set email alerts
|

Barley Cultivar, Kernel Composition, and Processing Affect the Glycemic Index

Abstract: Barley has a low glycemic index (GI), but it is unknown whether its GI is affected by variation in carbohydrate composition in different cultivars and by food processing and food form. To examine the effect of these factors on GI, 9 barley cultivars varying in amylose and β-glucan content were studied in 3 experiments in separate groups of 10 healthy participants. In Expt. 1, 3 barley cultivars underwent 2 levels of processing: hull removal [whole-grain (WG)] and bran, germ, and crease removal [white pearled (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…These findings are consistent with those of Liljeberg et al [43] who showed that, when breads are matched for insoluble fiber (12.1%-13.6%), increasing their β-glucan content from 11% to 15% did not affect the acute glycemic response in healthy adults. Aldughpassi and colleagues [44] also came to a similar conclusion when they investigated the glycemic impact of a range of different barley varieties and showed that the most significant characteristic that correlated with GI was grain total dietary fiber content (r = −0.75, P = .002) rather than β-glucan content (r = −0.44, n = 14, P = .11). These studies suggest that, unlike β-glucan isolates, wholegrain- Values are means ± SEM.…”
Section: Discussionmentioning
confidence: 65%
“…These findings are consistent with those of Liljeberg et al [43] who showed that, when breads are matched for insoluble fiber (12.1%-13.6%), increasing their β-glucan content from 11% to 15% did not affect the acute glycemic response in healthy adults. Aldughpassi and colleagues [44] also came to a similar conclusion when they investigated the glycemic impact of a range of different barley varieties and showed that the most significant characteristic that correlated with GI was grain total dietary fiber content (r = −0.75, P = .002) rather than β-glucan content (r = −0.44, n = 14, P = .11). These studies suggest that, unlike β-glucan isolates, wholegrain- Values are means ± SEM.…”
Section: Discussionmentioning
confidence: 65%
“…Food formats Intact boiled kernels were used in six studies, as is, fermented, pearled or baked into wheat bread. 9,29,32,36,43,44 Where the integrity of the kernel was maintained, 96% (21/22) treatments showed efficacy with an average reduction in AUC of 99±20 mmol Á min/l. The glycaemic response to intact boiled barley was shown to be related to total dietary fibre and slowly digestible starch, rather than b-glucan content.…”
Section: Implications For Persons With Type 2 Diabetesmentioning
confidence: 99%
“…The glycaemic response to intact boiled barley was shown to be related to total dietary fibre and slowly digestible starch, rather than b-glucan content. 32 This difference from processed products suggests that, for cooked kernels, the intact cell walls act as a physical barrier to starch-degrading enzymes.…”
Section: Implications For Persons With Type 2 Diabetesmentioning
confidence: 99%
“…High β-glucan and waxy phenotypes are regarded unfavorable for brewing and feed stuff, but they are considered to be a valuable source of soluble fiber in human diets showing potential functions in reducing GI and serum cholesterol levels, flattening the postprandial blood glucose levels and insulin rises (Thondre and Henry, 2009; Ahmad et al, 2012). The ability of β-glucan to lower the GI is dependent on the barley starch type (Finocchiaro et al, 2012) and other grain chemicals, especially the total content of fiber (Aldughpassi et al, 2012). …”
Section: Introductionmentioning
confidence: 99%